RUMAH RISHA SEBAGAI IMPLEMENTASI MITIGASI BENCANA GEMPA LOMBOK TAHUN 2020 - Susanto, Heri; Zuryani, Nazrina; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
The 2018 Lombok earthquake brought earthquake-resistant buildings such as the houses of RISHA, RIKA and RISBA to reduce the risk of unpredictable earthquakes. This study aims to describe and analyze how to mitigate and support and inhibit factors in mitigation through the post-earthquake RISHA development program using descriptive-explanative qualitative methods. The Public Works Agency recommends that earthquake disaster mitigation in Lombok be implemented through procedures for restoring and building RISHA houses during and after an earthquake. The supporting factors for the construction of the RISHA house involve all elements of society, such as POKMAS, facilitators, community assistance teams, mobilization of the TNI and Polri and collaboration with PT. Waskita Karya. Inhibiting factors are the slow formation of POKMAS, data on damaged houses that are not yet valid and continue to increase, lack of public trust in facilitators, lack of RISHA panels, and slow procurement and distribution of building materials. Keywords: RISHA’s House, Implementaton, Disaster Mitigation